REPRESENTASI PEREMPUAN DI FILM PERSEPOLIS DALAM PERSEPEKTIF ISLAM : (Analisis Semiotika Model John Fiske) - Sulton Abhitya Dirgantaradewa; Dyah Pithaloka (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
A film is a work of art that displays various types of meanings displayed through visuals and audio, which can have a significant effect on humans as the audience, often displaying phenomena that occur in various aspects of life. The Persepolis film depicts how the Iranian proletariat lived at that time, where the women depicted in the film embraced feminism. The purpose of this study was to determine how the representation of women in the Persepolis film through an Islamic perspective, which will be analyzed using John Fiske's semiotics. In order to produce in-depth results, the researcher used John Fiske's theory of semiotics with 3 coding levels, namely the level of reality which consists of appearance, clothing, behavior and expression, then the level of representation which consists of action, dialogue, conflict, background and music and ideological level. This study uses qualitative research methods with the aim of knowing the representation of women in the Persepolis film. The results found through the 3 levels are dominated by appearances, expressions, and actions that represent situations. There are acts of feminism, there is Westernization and moral degradation. Feminist actions that are carried out continuously leading to western feminism will result in a person behaving negatively. Like wanting to be a leader, not wanting to wear the veil, wanting to be completely equal as men.